Book Review: Panji Boma: Love, Throne, and Ambition, By Andri Noviadi. Tasikmalaya, Reference Style 2023, 182 pages, ISBN: 9786238295135, 80.000 Rupiah - Wijayanti, Yeni (Interdisciplinary International Journal of Conservation and Culture, 2023)
Panji Boma’ tells the story of the life journey of a main character named Panji Boma from the Dayeuhluhur Kingdom with his complicated love and his acts in power. A child who was born into a kingdom and was expected to become a wise and wise leader and bring prosperity to his region actually at the end of his life's journey created misery for the community which ended in a tragic death.